PENERAPAN STRATEGI PEMBELAJARAN AKTIF QUESTION STUDENT HAVE UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMAN 1 KAMPAR TIMUR - Rizkha Fatma Sari; Betty Holiwarni; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research to increase student’s active achievement on the subject of hydrocarbon in class X of SMA Negeri 1 Kampar Timur through the implementation of the active learning strategy Question Student Have. Form of the research is experiment research with pretest- posttest design. The sample consisted of to classes, X.8 class as experiment class and X.7 class as control class that randomly selected after testing normaly and homogenity. Experiment class was given by implementing active learning strategy Question Student Have and the control class was given by conventionl method. Analysis of data used t-test. Data of research obtined tcount> ttable (2,75> 1,66). It means that using active learning strategy Question Student Have can improve achievement on the subject of hydrocarbon in class X of SMA Negeri 1 Kampar Timur. Influence of increase student’s achievement 10,57%.Keywords: Active Learning Strategy, Question Student Have, Learning Achievement, Hydrocarbon